Characteristic of Demography, Economics Factors and Poverty in Gunung Kidul Regency - Suripto Suripto (Economic Journal of Emerging Markets, 2009)
This paper aims to analyze the determinants of poverty in Gunungkidul Regency in 2006. Itanalyses SUSENAS data using the logit model with the estimation method of Maximum LikelihoodEstimator (MLE). The variables included in the model are the characteristics of demography,economic factors, residential region and business loan. The result shows thatpoverty in Gunungkidul Regency is associated with residential region, household size, levelof employment in agricultural sector, level of education, and the age of household’s head. Italso shows that household size is the main source of poverty. In addition, business loan is ofimportant determinant factors in poverty reduction.Keywords: demography, poverty, household size, business loan